The Impact Of Pandemic Covid-19 On Online Learning Activities From April To July 2020 In Institut Stiami, Jakarta - Redjeki Agoestyowati (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Many people have known that Covid-19 has changed the world in all aspects. One of the aspect is education. It has made a lot of changing in transferring knowledge drastically, because lecturing was given online, attendance list was checked by program, examination was done by application. This research will describe about teaching and learning activities during the Pandemic of Covid 19 in Institut Stiami, Jakarta. Data collection was taken by interviewing some students by using zoom, google meet, WhatsApp, SSO (Single Sign On) of Institut Stiami or other Application. WhatsApp and Zoom are the application that often used in the Teaching and Learning Process. One of the biggest problem during online learning is about internet pulse or quota and connection is up and down sometimes. However, most of the students concluded that they enjoy learning online and during pandemic (Covid-19) and the teaching-learning activities ran quite well. During the lesson, some problem appeared such as technology, technical problem, internet connection, communication, etc., but all can be solved